2020
DOI: 10.21203/rs.3.rs-37469/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Stepped Majority Voting for Efficient EEG based Emotion Classification

Abstract: In this paper, a novel approach that is based on two-stepped majority voting is proposed for efficient EEG based emotion classification. Emotion recognition is important for human-machine interactions. Facial-features and body-gestures based approaches have been generally proposed for emotion recognition. Recently, EEG based approaches become more popular in emotion recognition. In the proposed approach, the raw EEG signals are initially low-pass filtered for noise removal and band-pass filters are used for rh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Tripathi et al [7 ], and Zhu Zhuang et al [14 ] reported accuracy scores in the range of 70.0 and 75.0%, respectively. The worst accuracy score was also reported by Ismael et al [13 ].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Tripathi et al [7 ], and Zhu Zhuang et al [14 ] reported accuracy scores in the range of 70.0 and 75.0%, respectively. The worst accuracy score was also reported by Ismael et al [13 ].…”
Section: Resultsmentioning
confidence: 60%
“…Rozgić et al [11 ] and Zhang et al [8 ] reported accuracy scores among 76.9 and 75.2% and Zhu Zhuang et al [14 ] and Candra et al [10 ] reported achievements between 60.0 and 70.0%. The worst score 57.6% was reported by Ismael et al [13 ].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Many studies have shown that there is a certain emotional dependence between each channel [11][12], while the traditional recurrent network can only capture the characteristics of the timing of EEG signals, and lacks the modeling of the relationship between channels, resulting in Feature learning ability is limited. This paper combines self-attention and simple recurrent unit module [13] (Simple Recurrent Unit, SRU), and proposes a built-in self-attention simple recurrent unit (BASRU).…”
Section: Built-in Self-attention Simple Recurrent Unitmentioning
confidence: 99%